2020
DOI: 10.1016/j.neuropharm.2020.108163
|View full text |Cite
|
Sign up to set email alerts
|

Comparing dopamine release, uptake, and D2 autoreceptor function across the ventromedial to dorsolateral striatum in adolescent and adult male and female rats

Abstract: Adolescents have increased vulnerability for the development of a range of psychiatric disorders, including substance abuse disorders (SUD) and mood disorders. Adolescents also have increased rates of sensation seeking and risk taking. The mesolimbic dopamine system plays a role in all these behaviors and disorders and reorganization of the dopamine system during adolescence may be important in mediating these developmental changes in behavior and vulnerability. Here, we used ex vivo fast scan cyclic voltammet… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 45 publications
1
15
2
Order By: Relevance
“…In the present report, we utilized ex vivo FSCV to compare stimulated dopamine release and its regulation in the NAc core of adult and adolescent male rats. Replicating our previous findings (Pitts et al, 2020), we see decreased stimulated dopamine release in the NAc core of male early adolescent rats. We also found this decrease in stimulated dopamine release is not driven by differences in release probability or transporter function (i.e.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In the present report, we utilized ex vivo FSCV to compare stimulated dopamine release and its regulation in the NAc core of adult and adolescent male rats. Replicating our previous findings (Pitts et al, 2020), we see decreased stimulated dopamine release in the NAc core of male early adolescent rats. We also found this decrease in stimulated dopamine release is not driven by differences in release probability or transporter function (i.e.…”
Section: Discussionsupporting
confidence: 90%
“…While reports examining extracellular levels of dopamine in the striatum show both lower and higher levels of dopamine during adolescence (Badanich et al, 2006;Cao et al, 2007;Philpot et al, 2009), sub-second stimulated dopamine release is consistently found to be decreased in the striatum of adolescent rats (Stamford, 1989;Palm and Nylander, 2014;Pitts et al, 2020). We have previously shown that stimulated dopamine release is decreased in the nucleus accumbens (NAc) core of early adolescent male rats (Pitts et al, 2020), yet, what mechanism is differentially mediating dopamine release in adolescent and adult rats is still unclear.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Motivated actions are mediated by dopamine release from the terminals. Mechanisms that govern dopamine release and volume transmission may be different in adults and adolescents (Robinson et al, 2011; Pitts et al, 2020). Our observation of increased dopamine neuron phasic response to reward in Pavlovian conditioning but decreased, phasic response in operant conditioning could be functionally amplified or muted if dopamine release is different in response to similar phasic activation of these neurons.…”
Section: Resultsmentioning
confidence: 99%
“…Much like in mammals, lamprey’s SNc/VTA dopaminergic neurons express D 2 receptors [ 3 ]. Dopamine release in the SNc/VTA is controlled by D 2 autoreceptors [ 53 ], and this mechanism is therefore very likely present in lampreys as well. The lamprey SNc/VTA population consists of around 600 dopaminergic neurons [ 41 ], a seemingly low number, but which is in line with the percentage of SNc/VTA neurons found in mammals, not taking the large cortical expansion into account in the latter [ 41 , 54 ].…”
Section: The Snc/vta At the Base Of Vertebrate Evolutionmentioning
confidence: 99%